PENINGKATAN KETERAMPILAN MEMBACA PUISI SISWA MENGGUNAKAN METODE PROBLEM SOLVING KELAS VIIIC SMP KEMALA BHAYANGKARI - Swandi CA, Yosepianus; Priyadi, Totok; Salem, Laurensius (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractÂ This research is in the beckground of this weaknes of student skill SMP Kemala Bhayangkari river in reading poetry.The type of research used is classroom action research (PTK) which has been done in two cyles. Qualitative research from and descriptive methods.The data source of this research is planning execution, observation and result of poetry reading.The technique which carried out in this research is obtained from that research average value of student learning result at pretes with average 19,80.Results of student in cyle I the use of problem solving method has inceased with an average of 76,15 the value of cyle pad II with an average79,23 based on the results of reding the poetry of studens.From cyle I to cyle II also increased.Â Keywords:Read poetry problem solving method